Implementasi Algoritma Pada Perancangan Database E-Commerce (Studi Kasus Toko Prabu Computer) - Suhartini Suhartini; Yuntari Purbasari; Essy Malays Sari Sakti (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2023)
Prabu Computer Store is a store engaged in the sale of computers, laptops, printers, spare parts, accessories and also servicing laptops, computers, printers. This store strives to meet the needs of its customers in the electronics sector, because along with the development of technology, computers, laptops, printers have not only become a tool that can make work easier but have become a necessity for the community both to complete work and for students, especially now that school exams are also based computer, that's why the demand for goods increases. The Prabu Computer store is still selling conventionally where buyers have to come directly to the store to see the items being sold, select, or pay for the items purchased, this causes less efficient service to customers, customers sometimes have to wait a long time to buy an item. That's why to save time and provide the best service to customers with a wider scope it is necessary to create a system at this store. Algorithm implementation in Prabu Computer's E-Commerce Design is carried out using the Prototype model and UML Database modeling designed to facilitate all transactions in Prabu Computer's E-Commerce.